Tokoh Lintas Agama Merawat Kerukunan Umat (Belajar Multikultural Dari Kota Malang) - Ikhwan, M. (LP2M IAIN Palopo, 2020)
Abstract[English]:Â This study explains the experience of interfaith leaders in realizing religious harmony in Malang. The theory will be used the idea of spiritual connection and the meaning of religious peace on sharia and human rights theory. This study uses a qualitative method with a phenomenological research approach. The research subject is an interfaith figure in Malang, who is incorporated in the Religious Harmony Forum (FKUB). The type of data presented is primary data from the results of in-depth interviews with the research subjects. The data that has been collected is analyzed in five stages, namely transcribing data as it is, reducing and eliminating data, classifying data, validating data, and making a description as a final report. The results of this study are twofold: The first, Malang City interfaith leaders are active in anticipating and resolving conflicts and maintaining religious harmony that has been created in various ways such as dialogue, silaturrahim and cooperation. The second, the interfaith leaders of Malang interpret religious harmony by mutual tolerance, mutual respect, and mutual freedom in terms of social and humanity but still in their faith by not uniting them.Abstrak[Indonesia]:Â Penelitian in menjelaskan pengalaman tokoh lintas agama dalam mewujudkan kerukunan umat beragama di Kota Malang. Teori yang akan digunakan adalah teori kerukunan umat beragama, teori hukum islam dan hak asasi manusia. Penelitian ini menggunakan metode kualitatif dengan pendekatan penelitian fenomenologi. Subjek penelitiannya adalah tokoh lintas agama di Kota Malang yang tergabung di Forum Kerukunan Umat Beragama (FKUB). Jenis data yang disajikan adalah data primer dari hasil wawancara mendalam dengan para subjek penelitian. Data yang telah terkumpul dianalisis dengan lima tahapan yaitu mentranskrip data apa adanya, mereduksi dan mengeliminasi data, mengklasifikasi data, memvalidasi data, dan membuat deskripsi sebagai laporan akhir. Adapun hasil penelitian ini ada dua: Pertama, tokoh lintas agama Kota Malang aktif dalam mengantisipasi dan menyelesaiakan konflik serta memelihara kerukunan umat beragama yang sudah tercipta dengan berbagai cara seperti berdialog, silaturrahim dan gotong royong. Kedua, tokoh lintas agama Kota Malang memaknai kerukunan umat beragama dengan saling toleran, saling menghormati, dan saling memberi kebebasan dalam hal sosial dan kemanusiaan namun tetap dalam iman masing-masing dengan tidak menyatukannya. Â